Pelestarian Tradisi Wonge Pada Masyarakat Kelurahan Tubo Sebagai Metode Merawat Kearifan Lokal - Gafur, Harun; Ely, Sulastri (Peneliti.net, 2024)
Based on the background that has been described, the identification of the problem is the low sense of love for the motherland, especially local traditions in Tubo Village, Ternate City, which results in the shifting of existing traditional values. The formulation of the problem is how the implementation of the Wonge tradition in the Tubo Village is one of the ways to maintain local wisdom, what efforts are made by the community to preserve the wonge tradition in the Tubo Village and what values are contained in the Wonge tradition in the Tubo Village. The problem is that the tradition that is the focus of this research is the Wonge tradition, the discussion is only limited to Tobu Village, Ternate City and the values contained in the Wonge tradition in the Tubo community. The purpose of this study is to find out the implementation of the Wonge tradition in the Tubo Village, Ternate city, to find out the community's efforts in preserving the wonge tradition in the Tubo Village, Ternate city and to find out the value contained in the wonge tradition in the Tubo Village, Ternate city. This type of research is qualitative research using an ethnographic approach. Qualitative research emphasizes meaning rather than generalization. The technique of determining research subjects by using sampling (Purposive Sampling) is used if the researcher has certain considerations in taking the sample. The subjects of this study were traditional leaders, religious leaders, traditional leaders and members of the Tubo Village community who still carry out wonge traditions. Tubo sub-district government, and the community. The results of this study concluded that, in carrying out the Wonge tradition it is carried out depending on the needs of the patient or sick person and is usually carried out by the family and administrators from the tradition, and there are also traditional leaders who are involved because it is a duty of custom. For us, as a community, we always help even though no notification or invitation has been officially conveyed, because this is our custom, the people of Tubo Village, when other people are in trouble